SALAT SEBAGAI SARANA PEMBINAAN DAN PENDIDIKAN KARAKTER ISLAMI - Maulana Ahadi; Nurul Huda (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The focus of this research was to find out the benefits of prayer for Islamic character building and education, a qualitative method was used in this study with library research data collection techniques, and from the research it was found that the implementation of prayer is very influential as a medium in building one's character, where prayer is not just a form of ritual which is carried out as an obligation as a servant to the Creator, but the prayer should be carried out with the utmost solemnity, and carry it out with full awareness and patience so that the prayer is not performed solely as a mere fulfillment of the obligation, but with the full awareness that deep, contains an educational function for fellow human beings, by carrying out the correct prayers, it will produce the meaning of worship and be able to form a character, both spiritually, emotionally, socially, and intellectually intelligent.